Neuropsychiatric Symptoms in Parkinson's Disease After Subthalamic Nucleus Deep Brain Stimulation - Liu, Weibing; Yamamoto, Tatsuya; Yamanaka, Yoshitaka; Asahina, Masato; Uchiyama, Tomoyuki; Hirano, Shigeki; Shimizu, Keisuke; Higuchi, Yoshinori; Kuwabara, Satoshi (Frontiers in Neurology, 2021)
Background: Indications for subthalamic nucleus deep brain stimulation (STN-DBS) surgery are determined basically by preoperative motor function; however, postoperative quality of life (QOL) is not necessarily associated with improvement in motor symptoms, suggesting that neuropsychiatric symptoms might be related to QOL after surgery in patients with Parkinson’s disease. Objectives: We aimed to examine temporal changes in neuropsychiatric symptoms and their associations to QOL after STN-DBS. Materials & Methods: We prospectively enrolled a total of 61 patients with Parkinson’s disease (mean age, 65.3 ± 0.9 years; mean disease duration, 11.9 ± 0.4 years). Motor function, cognitive function, and neuropsychiatric symptoms were evaluated before and after DBS surgery. Postoperative evaluation was performed 3 months, 1 year, and 3 years after surgery. Results: Of the 61 participants, 54 completed postoperative clinical evaluation after 3 months, 47 after 1 year, and 23 after 3 years. Frontal lobe functions, depression, and verbal fluency significantly worsened 3 years after STN-DBS. Nonmotor symptoms such as impulsivity, the unified PD rating scale (UPDRS) part I score was associated with QOL after STN-DBS. Conclusions: Frontal lobe functions, depression, and verbal fluency significantly worsened 3 years after STN-DBS. The score of UPDRS part I and higher impulsivity might be associated with QOL after STN-DBS.